Teachers’ Strategies to Design Media to Implement Communicative Leaning in Public Schools - M. Nur Mustafa; Hermandra Hermandra; Zulhafizh Zulhafizh (Universitas Riau, 2019)
In order to implement communicative learning activities, a teacher must be able to design various means or media so that learning process keeps running well. A teacher is expected not to stutter in designing media for various learning needs. The main purpose of this study is to examine the strategies done by teachers in designing media to implement communicative learning. This research is a descriptive research in which the data were collected from teachers of Madrasah Aliyah Negeri (public Islamic senior high schools) in Pekanbaru city. The research sample was 36 teachers. The instrument used to collect the data was a scale questionnaire. The data were descriptively analyzed. Each item of the questionnaire becomes the basis and the principal of the research analysis. The research findings reveal that to implement communicative learning, the teachers designed learning media. The strategies they used are making use of e-learning and making use of various teaching and learning facilities, creating student worksheets and compiling teaching materials, and presenting slides or other media in accordance with the teaching materials. Each of the strategy is set at a very high standard. The teachers’ strategy to design media at the public schools runs well. It can be seen from the average of the strategy that is 4.48 and the average belongs to very high category. The data also clearly reveal that the teachers are creative and innovative in designing media to implement communicative learning.